Developing JF standard-based digital grammar resources for intermediate Japanese language education: Research and best practices - Sarjani, Andi Irma; Iskandar, Ifan; Attas , Siti Gomo (Universitas Ahmad Dahlan, 2025)
Japanese language education in Indonesia faces critical challenges in intermediate grammar instruction regarding alignment with international standards, active learning integration, and digital resource availability. This study evaluates existing intermediate Japanese grammar materials against JF Standard requirements and develops a practical framework for creating digital resources. Employing design-based research methodology, this study analyzed materials from 10 Indonesian universities, conducted needs analysis surveys with 105 intermediate learners, developed the